2012
DOI: 10.1007/s00604-012-0787-4
|View full text |Cite
|
Sign up to set email alerts
|

Lead ion sensor with electrodes modified by imidazole-functionalized polyaniline

Abstract: Glassy carbon electrodes (GCE) and carbon paste electrodes (CPE) were modified with imidazole functionalized polyaniline with the aim to develop a sensor for lead (II) in both acidic and basic aqueous solution. The electrodes were characterized by cyclic voltammetry and differential pulse adsorptive stripping voltammetry. The limit of detections obtained with glassy carbon electrode and carbon paste electrode are 20 ng mL -1 and 2 ng mL -1 of lead ion, respectively. An interference study was carried out with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[ 88 ] developed a new copolymer poly(diphenylamine-co-2-aminobenzonitrile) and showed that it is efficient for detection of these ions down to 1.26 ppm and 0.26 ppm, respectively ( Figure 7 B). Copolymers of aniline and imidazole were also reported to present a high sensitivity toward Pb 2+ (2 µg·L −1 ) [ 89 ]. In another interesting example, authors described an electrode modified with overoxidized 2-mercaptoethanesulfonate (MES)-tethered polypyrrole, Nafion and bismuth, by analogy with bismuth thin-film electrodes described in Section 3.4 of this review [ 90 ].…”
Section: Conducting Polymer-modified Electrodesmentioning
confidence: 99%
“…[ 88 ] developed a new copolymer poly(diphenylamine-co-2-aminobenzonitrile) and showed that it is efficient for detection of these ions down to 1.26 ppm and 0.26 ppm, respectively ( Figure 7 B). Copolymers of aniline and imidazole were also reported to present a high sensitivity toward Pb 2+ (2 µg·L −1 ) [ 89 ]. In another interesting example, authors described an electrode modified with overoxidized 2-mercaptoethanesulfonate (MES)-tethered polypyrrole, Nafion and bismuth, by analogy with bismuth thin-film electrodes described in Section 3.4 of this review [ 90 ].…”
Section: Conducting Polymer-modified Electrodesmentioning
confidence: 99%
“…These authors achieved selective sensing of Pb 2+ ion with a detection limit of 2.7 × 10 −9 M concentration. In another study [19] a CPE was modified with a Schiff base molecule for Cu 2+ determination in the concentration range of 1.0 × 10 −8 to 1.0 × 10 −1 M. Studies have also been carried out with other polymer modified CPEs for the detection of Pb 2+ and other metal ions [20,21]. Iminodiacetic acid (IDA), as a selective metal coordinating ligand, has been used for remediation of lead [22] as well as for other kinds of sensing applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The detection of metal ions using conducting polymers can be improved by modification of electrode surfaces through various chemical methods and functionalization techniques. 23,24 When functional groups are sited on a polymer surface, they can perform various functions such as catalysis, sensing, and chemiluminescence. 21 Furthermore, functionalized surfaces have the smart ability to change their physical and chemical structures on exposure to specific stimuli.…”
Section: Introductionmentioning
confidence: 99%